2014
DOI: 10.3389/fcimb.2014.00119
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharides in diazotrophic bacteria

Abstract: Biological nitrogen fixation (BNF) is a process in which the atmospheric nitrogen (N2) is transformed into ammonia (NH3) by a select group of nitrogen-fixing organisms, or diazotrophic bacteria. In order to furnish the biologically useful nitrogen to plants, these bacteria must be in constant molecular communication with their host plants. Some of these molecular plant-microbe interactions are very specific, resulting in a symbiotic relationship between the diazotroph and the host. Others are found between ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…This finding is informative for clinical application because the cycle of endotoxin release from bacterial biofilms in environments such as dialysis pipes is still unclear. Endotoxins are produced when gram-negative bacteria die 20 ; the present study suggested that a weekly frequency, as opposed to a monthly one, is more appropriate for the disinfection of pipes against bacterial contamination. Moreover, endotoxins are also known to be toxic for dialysis patients and can enter the bloodstream through membrane pores.…”
Section: Discussionmentioning
confidence: 74%
“…This finding is informative for clinical application because the cycle of endotoxin release from bacterial biofilms in environments such as dialysis pipes is still unclear. Endotoxins are produced when gram-negative bacteria die 20 ; the present study suggested that a weekly frequency, as opposed to a monthly one, is more appropriate for the disinfection of pipes against bacterial contamination. Moreover, endotoxins are also known to be toxic for dialysis patients and can enter the bloodstream through membrane pores.…”
Section: Discussionmentioning
confidence: 74%
“…As recently discussed, possession of an adaptable outer membrane may provide an important fitness advantage in this context (9). Rhizobia produce modified lipid A, a major component of the lipopolysaccharides (LPS) that make up the outer leaflet of the outer membrane (21, 22). These modifications trend toward increasing the hydrophobicity and other cohesive interactions that lead to a more robust outer membrane (23, 24).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to glycans from sea organisms and fungal cells, this Research topic included a mini review on the lipopolysaccharide from bacteria. Serrato ( 2014 ) has described the structure of diazotrophic bacteria and highlights the importance of these glycolipids in the microbe-plant interaction.…”
mentioning
confidence: 99%